Biochar mitigates arsenic-induced human health risks and phytotoxicity in quinoa under saline conditions by modulating ionic and oxidative stress responses. (15th October 2021) - Shabbir, Arslan; Saqib, Muhammad; Murtaza, Ghulam; Abbas, Ghulam; Imran, Muhammad; Rizwan, Muhammad; Naeem, Muhammad Asif; Ali, Shafaqat; Rashad Javeed, Hafiz Muhammad
Abstract: Arsenic (As) is a toxic metalloid and its widespread contamination in agricultural soils along with soil salinization has become a serious concern for human health and food security. In the present study, the effect of cotton shell biochar (CSBC) in decreasing As-induced phytotoxicity and human health risks in quinoa ( Chenopodium quinoa Willd.) grown on As-spiked saline and non-saline soils was evaluated. Quinoa plants were grown on As contaminated (0, 15 and 30 mg kg −1 ) saline and non-saline soils amended with 0, 1 and 2% CSBC. Results showed that plant growth, grain yield, stomatal conductance and chlorophyll contents of quinoa showed more decline on As contaminated saline soil than non-saline soil. The application of 2% CSBC particularly enhanced plant growth, leaf relative water contents, stomatal conductance, pigment contents and limited the uptake of As and Na as compared to soil without CSBC. Salinity in combination with As trigged the production of H2 O2 and caused lipid peroxidation of cell membranes. Biochar ameliorated the oxidative stress by increasing the activities of antioxidant enzymes (SOD, POD, CAT). Carcinogenic and non-carcinogenic human health risks were greatly decreased in the presence of biochar. Application of 2% CSBC showed promising results in reducing human health risks and As toxicity in quinoa grown on As contaminated non-saline and saline soils. Further research is needed to evaluate the role of biochar in minimizing As accumulation in other crops on normal as well as salt affected soils under field conditions. Graphical abstract: Image 1 Highlights: Role of cotton shell biochar (CSBC) in reducing As toxicity in quinoa was explored. Grain yield and physiological attributes severely declined in the absence of CSBC. 2% CSBC enhanced plant growth, grain yield and limited the uptake of As and Na. CSBC ameliorated the oxidative stress via overexpression of antioxidant enzymes. CSBC reduced the human health risks due to consumption of As contaminated grains. Abstract : Application of 2% CSBC showed promising results in reducing human health risks and As toxicity in quinoa grown on As contaminated normal and saline soils.